Opportunities for Brucellosis Control in Mexico: Views Based on the Sustainable Livelihoods Perspective - Oseguera Montiel, David; Frankena, Klaas; Udo, Henk; van der Zijpp, Akke (Frontiers in Veterinary Science, 2019)
Caprine brucellosis is a main constraint for small-scale goat husbandry systems in the Global South, as it negatively affects production parameters and the pathogen can be transmitted to humans. The aim of this manuscript is to point out opportunities for brucellosis control in a resource poor area. Experiences from 3 years of fieldwork with Mexican goat smallholders are used as an example. The study was conducted in two Mexican states, Jalisco and Michoacán, both within the Bajío region. Main opportunities for brucellosis control are discussed within a livelihoods context. Goat farming is an strategy which gives farmers a number of benefits; these are: food, cash, prestige, and a job. Goat farming is also a reason for some farmers to stay in their villages rather than migrate to the US. This livelihood strategy, however, is threatened by brucellosis, which is endemic in the goat population of the region: 38% of the goats are seropositive. Brucellosis control, however, is an opportunity for small-scale goat farmers to enhance farmers’ health and welfare. The socio-economic context is very important in planning a successful brucellosis control campaign. Control strategies should be planned considering the goat farming husbandry and the views of the farmers. Our financial analysis showed that control and eradication of brucellosis in goats in the study region is feasible.